Resin composition
Patent Information
- Application Number
- JP2024209922
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2039-06-26
AI Technical Summary
【0010】 本発明によれば、密着性に優れ、反り、モールド成形後のフローマークの発生、及びポストキュア後の樹脂表面のムラの発生を抑制された硬化物を得ることができる樹脂組成物;当該樹脂組成物を用いた回路基板、及び半導体チップパッケージ;を提供できる。
Smart Images

Figure 2025023211000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. Further, the present invention relates to a circuit board and a semiconductor chip package using the resin composition. [Background technology]
[0002] In recent years, the demand for high-performance electronic devices such as smartphones and tablet devices has been increasing, and accordingly, the insulating materials used in these small electronic devices are required to have higher performance. As such insulating materials, for example, those formed by curing a resin composition are known (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-82052 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been a demand for smaller semiconductor chip packages, and therefore there is a demand for thinner insulating or sealing layers used in the semiconductor chip packages. Since thinner insulating or sealing layers tend to be more susceptible to warping, there is a demand for insulating or sealing layers that can suppress warping.
[0005] In order to suppress warping, it is conceivable to add a liquid component or a component that relieves stress to the resin composition.
[0006] In this case, however, the adhesion to the conductor layer etc. may be poor, and flow marks may occur after molding, and unevenness may easily occur on the resin surface after post-curing.
[0007] The present invention has been made in view of the above problems, and has an object to provide a resin composition capable of giving a cured product having excellent adhesion and suppressing warping, the occurrence of flow marks after molding, and the occurrence of unevenness on the resin surface after post-cure; and a circuit board and a semiconductor chip package using the resin composition. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above-mentioned problems, the present inventors have found that by incorporating a predetermined amount of an epoxy resin having a predetermined epoxy equivalent into a resin composition, it is possible to obtain a cured product which has excellent adhesion and is suppressed in warping, in the occurrence of flow marks after molding, and in the occurrence of unevenness on the resin surface after post-curing, and have thus completed the present invention.
[0009] That is, the present invention includes the following. [1] (A-1) An epoxy resin having an epoxy equivalent of more than 400 g / eq. and not more than 1500 g / eq. (B) an inorganic filler, and (C) a curing agent, The content of the (A-1) component is 0.2% by mass or more and less than 3% by mass, when the total amount of non-volatile components in the resin composition is 100% by mass, A resin composition, the content of the component (B) being 70% by mass or more when the total amount of non-volatile components in the resin composition is taken as 100% by mass. [2] The resin composition according to [1], wherein the component (A-1) includes one or more skeletons selected from the group consisting of a fluorene skeleton, a butadiene skeleton, an isoprene skeleton, an alkyleneoxy skeleton, a siloxane skeleton, and a bisphenol skeleton. [3] The resin composition according to [1] or [2], further comprising (A-2) an epoxy resin having an epoxy equivalent of 400 g / eq. or less, or an epoxy resin having an epoxy equivalent of more than 1500 g / eq. [4] The resin composition according to any one of [1] to [3], wherein the component (C) contains an acid anhydride curing agent. [5] The resin composition according to any one of [1] to [4], wherein the resin composition is liquid. [6] The resin composition according to any one of [1] to [5], which is a resin composition for sealing or insulation. [7] A circuit board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [6]. [8] A semiconductor chip package comprising the circuit board described in [7] and a semiconductor chip mounted on the circuit board. [9] A semiconductor chip package comprising: a semiconductor chip; and a cured product of the resin composition according to any one of [1] to [6] that encapsulates the semiconductor chip. Effect of the Invention
[0010] According to the present invention, it is possible to provide a resin composition which can give a cured product having excellent adhesion and which is suppressed in terms of warping, the occurrence of flow marks after molding, and the occurrence of unevenness on the resin surface after post-cure; and a circuit board and a semiconductor chip package which use the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below with reference to the following embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0012] [Resin composition] The resin composition of the present invention is a resin composition comprising (A-1) an epoxy resin having an epoxy equivalent of more than 400 g / eq. and not more than 1500 g / eq., (B) an inorganic filler, and (C) a curing agent, in which the content of the (A-1) component is 0.2% by mass or more and less than 3% by mass when the non-volatile components in the resin composition are taken as 100% by mass, and the content of the (B) component is 70% by mass or more when the non-volatile components in the resin composition are taken as 100% by mass. By containing the (A-1), (B) and (C) components in combination and setting the contents of the (A-1) and (B) components within the specified ranges, the resin composition can obtain the desired effects of the present invention, that is, a cured product having excellent adhesion and suppressing warping, the occurrence of flow marks after molding, and the occurrence of unevenness on the resin surface after post-curing can be obtained.
[0013] Taking advantage of the excellent properties of the cured product of this resin composition, it can be preferably used as an insulating layer or a sealing layer for circuit boards and semiconductor chip packages, and can be particularly preferably used as a sealing layer.
[0014] The resin composition may further contain an optional component in combination with the (A-1) component, the (B) component, and the (C) component. Examples of the optional component include (A-2) an epoxy resin having an epoxy equivalent of 400 g / eq. or less, or an epoxy resin having an epoxy equivalent of more than 1500 g / eq., and (D) a curing accelerator. In this specification, the (A-1) component and the (A-2) component may be collectively referred to as "(A) epoxy resin". Each component contained in the resin composition will be described below.
[0015] <(A-1) Epoxy resin having an epoxy equivalent of more than 400 g / eq. and less than or equal to 1500 g / eq.> The resin composition contains, as the component (A-1), an epoxy resin having an epoxy equivalent of more than 400 g / eq. and not more than 1500 g / eq. Since the component (A-1) has an epoxy equivalent of more than 400 g / eq. and not more than 1500 g / eq., a cured product having a crosslink density in a specific appropriate range is obtained. For this reason, it is considered that the toughness of the cured product of the resin composition containing the component (A-1) is improved, and as a result, the adhesion is improved. In addition, by including the component (A-1) in the resin composition, the occurrence of curing shrinkage when the resin composition is cured is suppressed. As a result, it is considered that the amount of warping is suppressed.
[0016] The epoxy equivalent of the (A-1) component is greater than 400 g / eq., preferably 410 g / eq. or more, more preferably 420 g / eq. or more, and 1500 g / eq. or less, preferably 1000 g / eq. or less, more preferably 800 g / eq. or less, 500 g / eq. or less. By making the epoxy equivalent of the (A-1) component fall within this range, the desired effects of the present invention can be obtained. The epoxy equivalent can be measured according to JIS K7236, and is the mass of a resin containing one equivalent of an epoxy group.
[0017] The content of the (A-1) component is 0.2% by mass or more, preferably 0.3% by mass or more, more preferably 0.5% by mass or more, and less than 3% by mass, preferably 2.5% by mass or less, more preferably 2% by mass or less, and 1.5% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. By setting the content of the (A-1) component within this range, it is possible to lower the glass transition temperature of the resin composition and further suppress the amount of warping. In the present invention, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are taken as 100% by mass, unless otherwise specified.
[0018] From the viewpoint of obtaining the desired effects of the present invention, the component (A-1) preferably has one or more epoxy groups in one molecule, more preferably has two or more epoxy groups in one molecule, and even more preferably has three or more epoxy groups in one molecule.
[0019] The component (A-1) may be a liquid component (A-1) at a temperature of 20° C. or a solid component (A-1) at a temperature of 20° C. From the viewpoint of obtaining the desired effects of the present invention, the component (A-1) is preferably a liquid component. The component (A-1) may be used alone or in combination of two or more types.
[0020] The component (A-1) preferably contains, for example, one or more skeletons selected from the group consisting of a fluorene skeleton, a butadiene skeleton, an isoprene skeleton, an alkyleneoxy skeleton, a siloxane skeleton, and a bisphenol skeleton.
[0021] The alkyleneoxy skeleton refers to a structure having an alkyleneoxy group in which an alkylene group and an oxygen atom are bonded, and the alkylene group is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and even more preferably an alkylene group having 3 to 6 carbon atoms.
[0022] Examples of the bisphenol skeleton include bisphenol A type, bisphenol F type, bisphenol AD type, bisphenol S type, and 4,4'-(9-fluorenylidene)bisphenol type.
[0023] Among these, it is more preferable that the component (A-1) contains one or more skeletons selected from the group consisting of a fluorene skeleton, a butadiene skeleton, an alkyleneoxy skeleton, a siloxane skeleton, and a bisphenol skeleton.
[0024] Examples of commercially available products of the component (A-1) include "EG-280" and "EG-250" manufactured by Osaka Gas Chemicals Co., Ltd., "R-45EPT", "R-15EPT", "DLC-204", "EX-145", "EX-171", "EX-991L", "EX-992L", and "FCA-635" manufactured by Nagase ChemteX Corporation, "SR-PTMG" manufactured by Sakamoto Pharmaceutical Co., Ltd., "KF-105" manufactured by Shin-Etsu Chemical Co., Ltd., "EXA-4816" and "EXA-4850" manufactured by DIC Corporation, "EP-4003S" manufactured by ADEKA Corporation, "LCE-2615" manufactured by Nippon Kayaku Co., Ltd., and "YX-7400", "YX-7105", and "YX-7110" manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.
[0025] From the viewpoint of significantly achieving the desired effects of the present invention, the weight average molecular weight (Mw) of the component (A-1) is preferably at least 100, more preferably at least 250, and even more preferably at least 400, and is preferably at most 5000, more preferably at most 3000, and even more preferably at most 1500. The weight average molecular weight of the component (A-1) is the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).
[0026] <(A-2) Epoxy resins with an epoxy equivalent of 400 g / eq. or less, or epoxy resins with an epoxy equivalent of more than 1500 g / eq.> The resin composition may contain, as (A-2), an epoxy resin having an epoxy equivalent of 400 g / eq. or less, or an epoxy resin having an epoxy equivalent of more than 1500 g / eq. By including the component (A-2) in the resin composition, the effects of the present invention can be significantly obtained.
[0027] Examples of the (A-2) component include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, etc. The (A-2) component may be used alone or in combination of two or more.
[0028] The resin composition preferably contains, as the (A-2) component, an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the (A-2) component having two or more epoxy groups in one molecule to 100% by mass of the non-volatile components of the (A-2) component is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0029] The (A-2) component includes an (A-2) component that is liquid at a temperature of 20° C. and an (A-2) component that is solid at a temperature of 20° C. The resin composition may use a liquid (A-2) component as the (A-2) component, may use a solid (A-2) component, or may use a combination of a liquid (A-2) component and a solid (A-2) component. Among them, from the viewpoint of reducing the viscosity of the resin composition, it is preferable to use a liquid (A-2) component as the (A-2) component.
[0030] As the liquid component (A-2), a liquid component (A-2) having two or more epoxy groups in one molecule is preferable.
[0031] As the liquid component (A-2), bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins; alicyclic epoxy resins such as glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins such as alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, glycidyl amine type epoxy resins, and epoxy resins having a butadiene structure are preferred, and glycidyl amine type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, and alicyclic epoxy resins are more preferred.
[0032] Specific examples of the liquid component (A-2) include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidyl amine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; and Nippon Steel & Sumitomo Metal Chemical Co., Ltd. Examples of such epoxy resins include "ZX1059" manufactured by Nagase ChemteX Corporation (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "CEL-2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation; "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; and "EP3950L" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation. These may be used alone or in combination of two or more types.
[0033] As the solid (A-2) component, a solid (A-2) component having three or more epoxy groups in one molecule is preferable, and an aromatic solid (A-2) component having three or more epoxy groups in one molecule is more preferable.
[0034] As the solid component (A-2), preferred are bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, and tetraphenylethane type epoxy resins, and more preferred are biphenyl type epoxy resins.
[0035] Specific examples of the solid component (A-2) include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", and "HP-7200H" (dicyclo pentadiene type epoxy resins; "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthylene ether type epoxy resins) manufactured by DIC; "EPPN-502H" (trisphenol type epoxy resins) manufactured by Nippon Kayaku; "NC7000L" (naphthol novolac type epoxy resins) manufactured by Nippon Kayaku; "NC3000H", "NC3000", and "N C3000L, NC3100 (biphenyl type epoxy resin); Nippon Steel & Sumitomo Metal Chemical's ESN475V (naphthol type epoxy resin); Nippon Steel & Sumitomo Metal Chemical's ESN485 (naphthol novolac type epoxy resin); Mitsubishi Chemical's YX4000H, YX4000, YL6121 (biphenyl type epoxy resin); Mitsubishi Chemical's YX4000HK (bixylenol type epoxy resin); Mitsubishi Chemical's YX Examples of epoxy resins include "PG-8800" (anthracene type epoxy resin), "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals, "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical, "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical, "jER1010" (solid bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical, and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical. These may be used alone or in combination of two or more.
[0036] When a liquid (A-2) component and a solid (A-2) component are used in combination as the (A-2) component, the ratio by mass (liquid (A-2) component:solid (A-2) component) is preferably 1:0.01 to 1:20, more preferably 1:0.05 to 1:10, and particularly preferably 1:0.1 to 1:1. When the ratio by mass of the liquid (A-2) component and the solid (A-2) component is within this range, the desired effects of the present invention can be significantly obtained.
[0037] When component (A-2) is an epoxy resin having an epoxy equivalent of 400 g / eq. or less, the epoxy equivalent is preferably 400 g / eq. or less, more preferably 300 g / eq. or less, even more preferably 200 g / eq. or less, and is preferably 50 g / eq. or more, more preferably 80 g / eq. or more, and even more preferably 90 g / eq. or more. When it is in this range, the crosslink density of the cured product of the resin composition is sufficient, and an insulating layer with small surface roughness can be obtained.
[0038] When component (A-2) is an epoxy resin having an epoxy equivalent of more than 1500 g / eq., the epoxy equivalent is preferably more than 1500 g / eq., more preferably 1600 g / eq. or more, even more preferably 1700 g / eq. or more, and is preferably 5000 g / eq. or less, more preferably 3000 g / eq. or less, and even more preferably 2000 g / eq. or less. When it is in this range, the crosslink density of the cured product of the resin composition is sufficient, and an insulating layer with small surface roughness can be obtained.
[0039] The weight average molecular weight (Mw) of the component (A-2) is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500, from the viewpoint of significantly achieving the desired effects of the present invention.
[0040] The content of the (A-2) component is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining an insulating layer exhibiting good mechanical strength and insulating reliability. The upper limit of the epoxy resin content is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention.
[0041] When the content of the nonvolatile components in the resin composition of component (A-1) is A1 when the total amount of nonvolatile components in the resin composition of component (A-2) is 100% by mass, and the content of the nonvolatile components in the resin composition of component (A-2) is A2 when the total amount of nonvolatile components in the resin composition is 100% by mass, from the viewpoint of prominently obtaining the effects of the present invention, A1 / A2 is preferably 0.01 or more, more preferably 0.03 or more, even more preferably 0.05 or more, and is preferably 1 or less, more preferably 0.8 or less, even more preferably 0.5 or less.
[0042] <(B) Inorganic filler> The resin composition contains an inorganic filler as component (B). By using the inorganic filler (B), the insulating performance of the cured product of the resin composition can be improved.
[0043] From the viewpoint of obtaining an insulating layer having excellent insulating performance, the content of the (B) inorganic filler is 70% by mass or more, preferably 75% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 88% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.
[0044] (B) An inorganic compound is used as the material of the inorganic filler. Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Moreover, as the silica, spherical silica is preferable. (B) The inorganic filler may be used alone or in combination of two or more types.
[0045] (B) Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denka Company, Ltd.; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.
[0046] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (B) inorganic filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, particularly preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less.
[0047] The average particle size of the inorganic filler (B) can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the volume-based particle size distribution of the inorganic filler (B) is measured using a flow cell method, and the average particle size is calculated from the obtained particle size distribution as the median diameter. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0048] The specific surface area of the (B) inorganic filler is preferably 1 m or less from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 3m 2 / g or more. There is no particular upper limit, but it is preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 The specific surface area is determined by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0049] (B) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.
[0050] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0051] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 parts by mass to 5 parts by mass of the surface treatment agent, more preferably 0.2 parts by mass to 3 parts by mass, and even more preferably 0.3 parts by mass to 2 parts by mass.
[0052] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity of the resin composition layer, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0053] The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.
[0054] When the content of the nonvolatile components in the resin composition of component (A-1) is A1 when the total amount of nonvolatile components is 100 mass%, and the content of the nonvolatile components in the resin composition of component (B) is B1 when the total amount of nonvolatile components is 100 mass%, from the viewpoint of prominently obtaining the effects of the present invention, A1 / B1 is preferably 0.001 or more, more preferably 0.005 or more, even more preferably 0.01 or more, and is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.1 or less.
[0055] <(C) Hardener> The resin composition contains a curing agent as component (C). The curing agent (C) usually has the function of reacting with component (A) to cure the resin composition. The curing agent (C) may be used alone or in combination of two or more kinds in any ratio.
[0056] As the (C) curing agent, a compound capable of reacting with the (A) epoxy resin to cure the resin composition can be used, and examples thereof include acid anhydride-based curing agents, amine-based curing agents, phenol-based curing agents, active ester-based curing agents, cyanate ester-based curing agents, benzoxazine-based curing agents, carbodiimide-based curing agents, etc. Among these, acid anhydride-based curing agents are preferred from the viewpoint of obtaining the effects of the present invention significantly.
[0057] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule.Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenone. Examples of the acid anhydride include tetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resins in which styrene and maleic acid are copolymerized. Commercially available acid anhydride curing agents may be used, such as "MH-700" manufactured by New Japan Chemical Co., Ltd.
[0058] The amine-based curing agent may be a curing agent having one or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propanediamine, and the like. bis(4-aminophenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. The amine-based curing agent may be a commercially available product, for example, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0059] The phenol-based curing agent may be a curing agent having one or more, preferably two or more, hydroxyl groups bonded to an aromatic ring (such as a benzene ring or a naphthalene ring) in one molecule. Among them, a compound having a hydroxyl group bonded to a benzene ring is preferred. From the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferred. From the viewpoint of adhesion, a nitrogen-containing phenol-based curing agent is preferred, and a triazine skeleton-containing phenol-based curing agent is more preferred. In particular, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac curing agent is preferred.
[0060] Specific examples of phenol-based curing agents and naphthol-based curing agents include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; and "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", "SN-375", and "SN-495V" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd. SN-395; DIC Corporation's "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165"; Gun-ei Chemical Co., Ltd.'s "GDP-6115L", "GDP-6115H", and "ELPC75", etc.
[0061] Examples of active ester curing agents include curing agents having one or more active ester groups in one molecule. Among them, the active ester curing agent is preferably a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred.
[0062] Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.
[0063] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0064] Preferred specific examples of the active ester curing agent include an active ester compound containing a dicyclopentadiene-type diphenol structure, an active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, and an active ester compound containing a benzoylated product of phenol novolac. Among them, an active ester compound containing a naphthalene structure and an active ester compound containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structure consisting of phenylene-dicyclopentylene-phenylene.
[0065] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000", "HPC-8000H", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L", "EXB-8000L-65TM", and "EXB-8150-65T" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "EXB-8100L-65T", "EXB-8150L-65T", and "EXB9416-70BK" (manufactured by DIC Corporation). IC Co., Ltd.); "DC808" (Mitsubishi Chemical Corporation) as an active ester compound containing an acetylated phenol novolac; "YLH1026" (Mitsubishi Chemical Corporation) as an active ester compound containing a benzoylated phenol novolac; "DC808" (Mitsubishi Chemical Corporation) as an active ester-based hardener which is an acetylated phenol novolac; "YLH1026" (Mitsubishi Chemical Corporation), "YLH1030" (Mitsubishi Chemical Corporation), and "YLH1048" (Mitsubishi Chemical Corporation) as active ester-based hardeners which are benzoylated phenol novolac; and the like.
[0066] Examples of cyanate ester curing agents include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester curing agents include "PT30" and "PT60" manufactured by Lonza Japan Co., Ltd. (both are phenol novolac type multifunctional cyanate ester resins); "ULL-950S" (multifunctional cyanate ester resin); "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer); and the like.
[0067] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0068] Specific examples of carbodiimide-based curing agents include "V-03", "V-05", and "V-07" manufactured by Nisshinbo Chemical Inc.; and Stavaxol (registered trademark) P manufactured by Rhein Chemie.
[0069] From the viewpoint of significantly obtaining the effects of the present invention, the content of the (C) curing agent, based on 100 mass% of the non-volatile components in the resin composition, is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.3 mass% or more, and is preferably 10 mass% or less, more preferably 8 mass% or less, even more preferably 7 mass% or less.
[0070] When the number of epoxy groups in the (A) component is taken as 1, the number of active groups in the (C) curing agent is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and preferably 2 or less, more preferably 1.8 or less, even more preferably 1.6 or less, and particularly preferably 1.4 or less. Here, the "number of epoxy groups in the (A) component" refers to the total value obtained by dividing the mass of the non-volatile components of the (A) component present in the resin composition by the epoxy equivalent. In addition, the "number of active groups in the (C) curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the (C) curing agent present in the resin composition by the active group equivalent. When the number of epoxy groups in the (A) component is taken as 1, the number of active groups in the (C) curing agent is within the above range, so that the desired effects of the present invention can be significantly obtained.
[0071] When the number of epoxy groups in the (A-1) component is taken as 1, the number of active groups in the (C) curing agent is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and preferably 2 or less, more preferably 1.8 or less, even more preferably 1.6 or less, and particularly preferably 1.4 or less. Here, the "number of epoxy groups in the (A-1) component" refers to the total value obtained by dividing the mass of the non-volatile components of the (A-1) component present in the resin composition by the epoxy equivalent. When the number of epoxy groups in the (A-1) component is taken as 1, the number of active groups in the (C) curing agent is within the above range, so that the desired effects of the present invention can be significantly obtained.
[0072] When the number of epoxy groups in the (A-2) component is taken as 1, the number of active groups in the (C) curing agent is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and preferably 2 or less, more preferably 1.8 or less, even more preferably 1.6 or less, and particularly preferably 1.4 or less. Here, the "number of epoxy groups in the (A-2) component" refers to the total value obtained by dividing the mass of the non-volatile components of the (A-2) component present in the resin composition by the epoxy equivalent. When the number of epoxy groups in the (A-2) component is taken as 1, the number of active groups in the (C) curing agent is within the above range, so that the desired effects of the present invention can be significantly obtained.
[0073] <(D) Curing accelerator> The resin composition may contain (D) a curing accelerator as an optional component. Examples of the curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. The amine-based curing accelerators and imidazole-based curing accelerators are preferred, and the amine-based curing accelerators are more preferred. The curing accelerators may be used alone or in combination of two or more.
[0074] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.
[0075] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0076] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.
[0077] As the imidazole-based curing accelerator, a commercially available product may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0078] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.
[0079] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0080] The content of the (D) curing accelerator, based on 100 mass% of the non-volatile components in the resin composition, is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and particularly preferably 0.05 mass% or more, and is preferably 1 mass% or less, more preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less.
[0081] <(E) Other Additives> The resin composition may further contain other additives as optional components in addition to the above-mentioned components. Examples of such additives include resin additives such as thermoplastic resins, flame retardants, organic fillers, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds, thickeners, defoamers, leveling agents, adhesion promoters, colorants, and pigments. These additives may be used alone or in combination of two or more at any ratio. The content of each additive can be appropriately set by a person skilled in the art.
[0082] The above-mentioned resin composition may contain a solvent as necessary, but is preferably a solvent-free resin composition that does not substantially contain a solvent. Even if it does not contain a solvent, the resin composition can be fluidized when molded using a compression molding method, and excellent compression moldability can be achieved. Therefore, this resin composition can be used as a solvent-free resin composition. "Substantially free of solvent" means, for example, that the content of the solvent is 1% by mass or less relative to the entire solvent-free resin composition.
[0083] The method for preparing the resin composition is not particularly limited, and examples thereof include a method in which the blending components are mixed and dispersed using a rotary mixer or the like, with the addition of a solvent or the like as necessary.
[0084] <Characteristics of resin composition> According to the above-mentioned resin composition, a layer of a cured product capable of suppressing warpage can be obtained. Therefore, by using this resin composition, a sealing layer and an insulating layer capable of suppressing warpage of a circuit board and a semiconductor chip package can be obtained. For example, using the above-mentioned resin composition, a cured product layer of the resin composition heated at 180°C for 90 minutes is formed on a 12-inch silicon wafer by the method described in the Examples, to prepare a sample substrate. In this case, the amount of warpage measured by the method described in the Examples at 25°C can be usually less than 5 mm, preferably less than 4 mm. The lower limit is not particularly limited, but may be 0.01 mm or more.
[0085] In addition, the above-mentioned resin composition can give a cured product with excellent adhesion. Therefore, by using this resin composition, a sealing layer and an insulating layer with excellent adhesion can be obtained for a circuit board and a semiconductor chip package. The adhesion strength is preferably 500 kgf / cm 2 The adhesion strength can be measured according to the method described in the Examples below.
[0086] A cured product using the above-mentioned resin composition exhibits the characteristic of suppressing the occurrence of flow marks after molding. Therefore, by using this resin composition, it is possible to obtain a sealing layer and an insulating layer in which the occurrence of flow marks is suppressed. Specifically, the resin composition is compression molded on a 12-inch silicon wafer using a compression molding device (mold temperature: 130°C, pressure: 6 MPa, cure time: 10 minutes) to form a resin composition layer with a thickness of 300 μm, and a sample is formed (the area of the resin composition layer at this time is 14.6 cm × 14.6 × 3.14 = 45.844 cm). 2 ) and observe the appearance of the resin composition layer of the sample. At this time, the area occupied by the flow marks is less than 20% of the entire surface of the resin composition layer. The occurrence of flow marks after molding can be evaluated according to the method described in the examples below.
[0087] Furthermore, the cured product using the above-mentioned resin composition exhibits the characteristic that the occurrence of resin surface unevenness after post-cure is suppressed. Therefore, by using this resin composition, it is possible to obtain a sealing layer and an insulating layer in which the occurrence of resin surface unevenness after post-cure is suppressed. Specifically, the resin composition is compression molded on a 12-inch silicon wafer using a compression molding device (mold temperature: 130°C, pressure: 6 MPa, cure time: 10 minutes) to form a resin composition layer with a thickness of 300 μm on the 12-inch silicon wafer (the area of the resin composition layer at this time is 14.6 cm x 14.6 x 3.14 = 45.844 cm). 2 After that, the resin composition layer is heated at 180° C. for 90 minutes, and the appearance of the cured layer obtained by thermally curing the resin composition layer is observed. At this time, the surface of the cured layer is usually uniform and free of color unevenness.
[0088] The resin composition may be liquid or solid, but is preferably liquid when molded. For example, a resin composition that is liquid at room temperature (e.g., 20°C) may be molded by compression molding at room temperature without any special temperature adjustment, or may be heated to an appropriate temperature and molded by compression molding. In addition, a resin composition that is liquid at room temperature may be filled into a cartridge, the resin composition may be discharged from the cartridge, and then molded by compression molding.
[0089] Furthermore, a resin composition that is solid at room temperature can usually be made liquid by adjusting the temperature to a higher temperature (e.g., 130°C), and can be molded by compression molding with appropriate temperature adjustment such as heating. The resin composition can usually be made liquid at an appropriate temperature even without containing a solvent, and can be used, for example, as a liquid sealant. Here, liquid refers to a composition having a viscosity of less than 1500 Pa s measured by the following measurement method. Using a RE80 viscometer (manufactured by Toki Sangyo Co., Ltd.), 0.2 to 0.3 ml of the resin composition to be measured is measured using a syringe. During measurement, the temperature of the measurement chamber of the viscometer is controlled at 25.0°C using an external circulation type thermostatic bath. The rotor speed is set to 1 rpm, and the viscosity is measured after 120 seconds.
[0090] Since the resin composition has the above-mentioned characteristics, it can be suitably used as a resin composition for sealing electronic devices such as organic EL devices and semiconductors, and in particular, it can be suitably used as a resin composition for sealing semiconductors (semiconductor sealing resin composition), preferably a resin composition for sealing semiconductor chips (semiconductor chip sealing resin composition). In addition, the resin composition can be used as a resin composition for an insulating layer other than sealing applications. For example, the resin composition can be suitably used as a resin composition for forming an insulating layer of a semiconductor chip package (a resin composition for an insulating layer of a semiconductor chip package) and a resin composition for forming an insulating layer of a circuit board (including a printed wiring board) (a resin composition for an insulating layer of a circuit board).
[0091] Examples of semiconductor chip packages include FC-CSP, MIS-BGA package, ETS-BGA package, Fan-out type WLP (Wafer Level Package), Fan-in type WLP, Fan-out type PLP (Panel Level Package), and Fan-in type PLP.
[0092] The resin composition may also be used as an underfill material, for example, as a material for MUF (Molding Under Filling) that is used after a semiconductor chip is connected to a substrate.
[0093] Furthermore, the resin composition can be used in a wide range of applications in which resin compositions are used, such as resin sheets, sheet-like laminate materials such as prepregs, solder resists, die bonding materials, hole filling resins, and component embedding resins.
[0094] [Resin sheet] The resin sheet of the present invention has a support and a resin composition layer provided on the support. The resin composition layer is a layer containing the resin composition of the present invention and is usually formed of a resin composition.
[0095] From the viewpoint of thinning, the thickness of the resin composition layer is preferably 600 μm or less, more preferably 550 μm or less, and even more preferably 500 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, or 200 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited and can be, for example, 1 μm or more, 5 μm or more, 10 μm or more, etc.
[0096] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0097] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"); polycarbonate (hereinafter sometimes abbreviated as "PC"); acrylic polymers such as polymethyl methacrylate (hereinafter sometimes abbreviated as "PMMA"); cyclic polyolefins; triacetyl cellulose (hereinafter sometimes abbreviated as "TAC"); polyether sulfide (hereinafter sometimes abbreviated as "PES"); polyether ketone; polyimide; and the like. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0098] When a metal foil is used as the support, examples of the metal foil include copper foil and aluminum foil. Among them, copper foil is preferable. As the copper foil, a foil made of a single metal of copper may be used, or a foil made of an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0099] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, an antistatic treatment or the like.
[0100] In addition, the support may be a support with a release layer having a release layer on the surface to be bonded to the resin composition layer. Examples of the release agent used in the release layer of the support with a release layer include one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. Examples of commercially available release agents include alkyd resin-based release agents such as "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation. Examples of the support with a release layer include "Lumirror T60" manufactured by Toray Industries, Inc.; "Purex" manufactured by Teijin Limited; and "Unipeel" manufactured by Unitika Limited.
[0101] The thickness of the support is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the total thickness of the support with a release layer is preferably in the above range.
[0102] The resin sheet can be produced, for example, by applying the resin composition onto a support using a coating device such as a die coater. If necessary, the resin composition may be dissolved in an organic solvent to prepare a resin varnish, and the resin sheet may be produced by applying the resin varnish. By using a solvent, the viscosity can be adjusted to improve the coatability. When the resin varnish is used, the resin varnish is usually dried after application to form a resin composition layer.
[0103] Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, and cyclohexanone; acetate ester solvents such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitol solvents such as cellosolve and butyl carbitol; aromatic hydrocarbon solvents such as toluene and xylene; amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone; etc. The organic solvent may be used alone or in combination of two or more kinds at any ratio.
[0104] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are such that the content of the organic solvent in the resin composition layer is usually 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30% by mass to 60% by mass of the organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0105] The resin sheet may include any layer other than the support and the resin composition layer as necessary. For example, in the resin sheet, a protective film similar to that of the support may be provided on the surface of the resin composition layer not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is, for example, 1 μm to 40 μm. The protective film can prevent the adhesion of dirt and the like to the surface of the resin composition layer and scratches. When the resin sheet has a protective film, the resin sheet can be used by peeling off the protective film. In addition, the resin sheet can be stored by being wound into a roll.
[0106] [Circuit board] The circuit board used in the present invention can be manufactured, for example, by a manufacturing method including the following steps (1) and (2). The cured product of the above-mentioned resin composition can be used as a sealing layer for semiconductor chips and the like on the circuit board as described below, and the cured product of the resin composition can also be used to form an insulating layer included in the circuit board. However, the insulating layer may be formed of a material other than the cured product of the above-mentioned resin composition. (1) A step of forming a resin composition layer on a substrate. (2) A step of thermally curing the resin composition layer to form an insulating layer.
[0107] In step (1), a substrate is prepared. Examples of the substrate include glass epoxy substrates, metal substrates (such as stainless steel and cold-rolled steel sheet (SPCC)), polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. The substrate may have a metal layer such as copper foil on the surface as a part of the substrate. For example, a substrate having a peelable first metal layer and a peelable second metal layer on both surfaces may be used. When such a substrate is used, a conductor layer as a wiring layer that can function as a circuit wiring is usually formed on the surface of the second metal layer opposite to the first metal layer. Examples of substrates having such a metal layer include "Micro Thin", an ultra-thin copper foil with a carrier copper foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0108] A conductor layer may be formed on one or both surfaces of the substrate. In the following description, a member including a substrate and a conductor layer formed on the substrate surface may be referred to as a "substrate with wiring layer" as appropriate. Examples of the conductor material included in the conductor layer include materials including one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor material may be a single metal or an alloy. Examples of the alloy include alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). Among them, from the viewpoints of versatility, cost, and ease of patterning in the formation of the conductor layer, chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper as single metals; and alloys of nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy as alloys; are preferred. Among these, the single metals chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver and copper; and nickel-chromium alloys; are more preferable, and the single metal copper is particularly preferable.
[0109] The conductor layer may be patterned, for example, to function as a wiring layer. In this case, the line (circuit width) / space (width between circuits) ratio of the conductor layer is not particularly limited, but is preferably 20 / 20 μm or less (i.e., pitch is 40 μm or less), more preferably 10 / 10 μm or less, even more preferably 5 / 5 μm or less, even more preferably 1 / 1 μm or less, and particularly preferably 0.5 / 0.5 μm or more. The pitch does not need to be the same throughout the conductor layer. The minimum pitch of the conductor layer may be, for example, 40 μm or less, 36 μm or less, or 30 μm or less.
[0110] The thickness of the conductor layer depends on the design of the circuit board, but is preferably 3 μm to 35 μm, more preferably 5 μm to 30 μm, further preferably 10 μm to 20 μm, and particularly preferably 15 μm to 20 μm.
[0111] The conductor layer can be formed, for example, by a method including a step of laminating a dry film (photosensitive resist film) on a substrate, a step of forming a pattern by exposing and developing the dry film under predetermined conditions using a photomask to obtain a patterned dry film, a step of forming a conductor layer by a plating method such as electrolytic plating using the developed patterned dry film as a plating mask, and a step of peeling off the patterned dry film. As the dry film, a photosensitive dry film made of a photoresist composition can be used, and for example, a dry film formed of a resin such as a novolac resin or an acrylic resin can be used. The lamination conditions of the substrate and the dry film can be the same as the lamination conditions of the substrate and the resin sheet described later. The peeling off of the dry film can be carried out using, for example, an alkaline peeling solution such as a sodium hydroxide solution.
[0112] After preparing the substrate, a resin composition layer is formed on the substrate. When a conductor layer is formed on the surface of the substrate, the resin composition layer is preferably formed so that the conductor layer is embedded in the resin composition layer.
[0113] The resin composition layer is formed, for example, by laminating a resin sheet and a substrate. This lamination can be performed, for example, by bonding the resin sheet to the substrate from the support side under heat and pressure, thereby laminating the resin composition layer to the substrate. Examples of the member for heat-pressing the resin sheet to the substrate (hereinafter, sometimes referred to as a "heat-pressing member") include a heated metal plate (such as a SUS plate) or a metal roll (such as a SUS roll). It is preferable to press the heat-pressing member through an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the substrate, rather than directly pressing the resin sheet.
[0114] The lamination of the substrate and the resin sheet may be carried out, for example, by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C. The thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa. The thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably carried out under reduced pressure conditions of a pressure of 13hPa or less.
[0115] After lamination, the laminated resin sheets may be smoothed under normal pressure (atmospheric pressure), for example, by pressing the support side with a thermocompression member. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The lamination and smoothing treatment may be performed successively using a vacuum laminator.
[0116] The resin composition layer may be formed from the resin sheet or resin composition of the present invention. When the resin composition layer is formed from the resin composition, the resin composition layer may be formed, for example, by a compression molding method. The resin composition may be filled in a cartridge and the resin composition may be discharged from the cartridge to form the resin composition layer. The molding conditions may be the same as those of the method for forming the resin composition layer in the step of forming the sealing layer of the semiconductor chip package described later.
[0117] After forming the resin composition layer on the substrate, the resin composition layer is thermally cured to form an insulating layer. The thermal curing conditions for the resin composition layer vary depending on the type of resin composition, but the curing temperature is usually in the range of 120°C to 240°C (preferably in the range of 150°C to 220°C, more preferably in the range of 170°C to 200°C), and the curing time is in the range of 5 minutes to 120 minutes (preferably in the range of 10 minutes to 100 minutes, more preferably in the range of 15 minutes to 90 minutes).
[0118] Before the resin composition layer is thermally cured, the resin composition layer may be subjected to a preheating treatment at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of usually 50° C. or more and less than 120° C. (preferably 60° C. or more and 110° C. or less, more preferably 70° C. or more and 100° C. or less) for usually 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).
[0119] In the manner described above, a circuit board having an insulating layer can be manufactured. The method for manufacturing a circuit board may further include any optional step. For example, when a circuit board is manufactured using a resin sheet, the manufacturing method of the circuit board may include a step of peeling off the support of the resin sheet. The support may be peeled off before or after the resin composition layer is thermally cured.
[0120] The method for manufacturing a circuit board may include, for example, a step of polishing the surface of the insulating layer after forming the insulating layer. The polishing method is not particularly limited. For example, the surface of the insulating layer can be polished using a surface grinder.
[0121] The manufacturing method of the circuit board may include, for example, a step of connecting the conductor layers between layers, that is, a step of drilling holes in the insulating layer. This allows holes such as via holes and through holes to be formed in the insulating layer. Examples of the method of forming the via holes include laser irradiation, etching, and mechanical drilling. The size and shape of the via holes may be appropriately determined depending on the design of the circuit board. The step of connecting the conductor layers between layers may also be performed by polishing or grinding the insulating layer.
[0122] After the via holes are formed, it is preferable to carry out a step of removing smears in the via holes. This step is sometimes called a desmear step. For example, when the conductive layer is formed on the insulating layer by a plating step, the via holes may be subjected to a wet desmear process. When the conductive layer is formed on the insulating layer by a sputtering step, a dry desmear process such as a plasma treatment process may be carried out. Furthermore, the insulating layer may be roughened by the desmear process.
[0123] Furthermore, before forming the conductor layer on the insulating layer, the insulating layer may be subjected to a roughening treatment. This roughening treatment usually roughens the surface of the insulating layer including the inside of the via hole. The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order.
[0124] After the via holes are formed, a conductor layer is formed on the insulating layer. By forming a conductor layer at the position where the via holes are formed, the newly formed conductor layer and the conductor layer on the surface of the substrate are electrically connected to each other, and interlayer connection is performed. Examples of methods for forming the conductor layer include plating, sputtering, and vapor deposition, and plating is preferred. In a preferred embodiment, the surface of the insulating layer is plated by an appropriate method such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. In addition, when the support in the resin sheet is a metal foil, a conductor layer having a desired wiring pattern can be formed by a subtractive method. The material of the conductor layer to be formed may be a single metal or an alloy. In addition, this conductor layer may have a single layer structure, or may have a multi-layer structure including two or more layers of different types of materials.
[0125] Here, an example of an embodiment in which a conductor layer is formed on an insulating layer will be described in detail. A plating seed layer is formed on the surface of the insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer, exposing a part of the plating seed layer corresponding to a desired wiring pattern. After forming an electrolytic plating layer on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by a process such as etching, and a conductor layer having a desired wiring pattern can be formed. Note that, when forming the conductor layer, the dry film used to form the mask pattern is the same as the above-mentioned dry film.
[0126] The method for manufacturing a circuit board may include a step of removing the substrate. By removing the substrate, a circuit board having an insulating layer and a conductor layer embedded in the insulating layer is obtained. The step of removing the substrate can be performed, for example, when a substrate having a peelable metal layer is used.
[0127] [Semiconductor chip package] The semiconductor chip package according to the first embodiment of the present invention includes the above-mentioned circuit board and a semiconductor chip mounted on the circuit board. The semiconductor chip package can be manufactured by bonding the semiconductor chip to the circuit board.
[0128] The bonding conditions between the circuit board and the semiconductor chip may be any conditions that allow conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the circuit board. For example, the conditions used in flip-chip mounting of the semiconductor chip may be used. Also, for example, the semiconductor chip and the circuit board may be bonded via an insulating adhesive.
[0129] An example of a bonding method is a method in which a semiconductor chip is pressure-bonded to a circuit board. Pressure-bonding conditions are a pressure-bonding temperature usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and a pressure-bonding time usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds).
[0130] Another example of the bonding method is a method of bonding a semiconductor chip to a circuit board by reflow. The reflow conditions may be in the range of 120°C to 300°C.
[0131] After the semiconductor chip is bonded to the circuit board, the semiconductor chip may be filled with a molded underfill material. As the molded underfill material, the above-mentioned resin composition or the above-mentioned resin sheet may be used.
[0132] The semiconductor chip package according to the second embodiment of the present invention includes a semiconductor chip and a cured product of the resin composition that encapsulates the semiconductor chip. In such a semiconductor chip package, the cured product of the resin composition usually functions as an encapsulation layer. An example of the semiconductor chip package according to the second embodiment is a fan-out type WLP.
[0133] The manufacturing method of a semiconductor chip package such as a fan-out type WLP is as follows: (A) a step of laminating a temporary fixing film on a substrate; (B) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (C) a step of laminating a resin composition layer of the resin sheet of the present invention on a semiconductor chip, or applying the resin composition of the present invention on a semiconductor chip and thermally curing the composition to form an encapsulating layer; (D) peeling the substrate and the temporary fixing film from the semiconductor chip; (E) a step of forming a rewiring formation layer (insulating layer) on the surface from which the substrate and the temporary fixing film of the semiconductor chip have been peeled off; (F) forming a conductor layer (rewiring layer) on a rewiring formation layer (insulating layer); and (G) forming a solder resist layer on the conductor layer. The method for manufacturing a semiconductor chip package may also include (H) dicing the plurality of semiconductor chip packages into individual semiconductor chip packages.
[0134] For details of the manufacturing method of such a semiconductor chip package, reference can be made to paragraphs 0066 to 0081 of International Publication No. 2016 / 035577, the contents of which are incorporated herein by reference.
[0135] A semiconductor chip package according to a third embodiment of the present invention is, for example, a semiconductor chip package according to the second embodiment, in which a rewiring formation layer or a solder resist layer is formed from a cured product of the resin composition of the present invention.
[0136] [Semiconductor Devices] Examples of semiconductor devices in which the above-mentioned semiconductor chip package is mounted include various semiconductor devices used in electrical products (e.g., computers, mobile phones, smartphones, tablet devices, wearable devices, digital cameras, medical equipment, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES
[0137] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the operations described below were performed in an environment of normal temperature and pressure, unless otherwise specified.
[0138] (Preparation of Silica A) Average particle size 7μm, specific surface area 3.4m 2 / g of spherical silica was surface-treated with KBM-573 (manufactured by Shin-Etsu Chemical Co., Ltd.) to obtain spherical silica A.
[0139] <Example 1> 5 parts of liquid epoxy resin ("ZX1059" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., a 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq.), 7 parts of glycidylamine type epoxy resin ("630" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 95 g / eq.), 2 parts of fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemical Co., Ltd., epoxy equivalent 460 g / eq.), 8 parts of acid anhydride-based curing agent ("MH-700" manufactured by New Japan Chemical Co., Ltd., 4-methylhexahydrophthalic anhydride / hexahydrophthalic anhydride=70 / 30), 140 parts of silica A, and 0.1 part of curing accelerator ("1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd.) were uniformly dispersed using a mixer to obtain resin composition 1.
[0140] <Example 2> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals, epoxy equivalent weight 460 g / eq.) was replaced with 2 parts of a liquid alkyleneoxy skeleton- and butadiene skeleton-containing epoxy resin ("EX-991L" manufactured by Nagase ChemteX Corporation, epoxy equivalent weight 450 g / eq.). Resin composition 2 was obtained in the same manner as in Example 1 except for the above.
[0141] <Example 3> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals Co., Ltd., epoxy equivalent weight 460 g / eq.) was replaced with 2 parts of a liquid alkyleneoxy skeleton-containing epoxy resin ("SR-PTMG" manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., epoxy equivalent weight 420 g / eq.). Resin composition 3 was obtained in the same manner as in Example 1 except for the above.
[0142] <Example 4> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals, epoxy equivalent weight 460 g / eq.) was replaced with 2 parts of a liquid siloxane skeleton-containing epoxy resin ("KF-105" manufactured by Shin-Etsu Chemical Co., Ltd., epoxy equivalent weight 490 g / eq.). Resin composition 4 was obtained in the same manner as in Example 1 except for the above.
[0143] <Example 5> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals, epoxy equivalent weight 460 g / eq.) was replaced with 2 parts of a bisphenol A skeleton-containing liquid epoxy resin ("EXA-4816" manufactured by DIC, epoxy equivalent weight 403 g / eq.). Resin composition 5 was obtained in the same manner as in Example 1 except for the above.
[0144] <Example 6> In Example 1, the amount of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals Co., Ltd., epoxy equivalent 460 g / eq.) was changed from 2 parts to 1 part. Resin composition 6 was obtained in the same manner as in Example 1 except for the above.
[0145] <Comparative Example 1> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals Co., Ltd., epoxy equivalent 460 g / eq.) was replaced with 2 parts of a liquid epoxy resin ("SR-14BJ" manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., epoxy equivalent 102 g / eq.). Resin composition 7 was obtained in the same manner as in Example 1 except for the above.
[0146] <Comparative Example 2> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemicals Co., Ltd., epoxy equivalent weight 460 g / eq.) was replaced with 2 parts of a liquid epoxy resin ("SR-16BJ" manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., epoxy equivalent weight 120 g / eq.). Resin composition 8 was obtained in the same manner as in Example 1 except for the above points.
[0147] <Comparative Example 3> In Example 1, 2 parts of the fluorene skeleton-containing epoxy resin ("EG-280" manufactured by Osaka Gas Chemical Co., Ltd., epoxy equivalent weight 460 g / eq.) was replaced with 2 parts of a liquid epoxy resin ("X-22-163B" manufactured by Shin-Etsu Chemical Co., Ltd., epoxy equivalent weight 1800 g / eq.). Resin composition 9 was obtained in the same manner as in Example 1 except for the above.
[0148] <Comparative Example 4> In Example 4, the amount of liquid epoxy resin ("KF-105" manufactured by Shin-Etsu Chemical Co., Ltd., epoxy equivalent 490 g / eq.) was changed from 2 parts to 5 parts. Resin composition 10 was obtained in the same manner as in Example 4 except for the above.
[0149] <Comparative Example 5> The amount of silica A in Example 2 was changed from 140 parts to 55 parts. Resin composition 11 was obtained in the same manner as in Example 2 except for the above-mentioned points.
[0150] <Warpage evaluation> Each resin composition produced in the examples and comparative examples was compression molded on a 12-inch silicon wafer using a compression molding device (mold temperature: 130°C, pressure: 6MPa, cure time: 10 minutes) to form a resin composition layer with a thickness of 300 μm. The resin composition layer was then heated at 180°C for 90 minutes to thermally cure. This resulted in a sample substrate including a silicon wafer and a cured layer of the resin composition. The amount of warping of the sample substrate at 25°C was measured using a shadow moire measuring device ("ThermoireAXP" manufactured by Akorometrix). The measurement was performed in accordance with JEITA EDX-7311-24, a standard of the Japan Electronics and Information Technology Industries Association. Specifically, a virtual plane calculated by the least squares method of all data on the substrate surface in the measurement area was used as a reference plane, and the difference between the minimum and maximum values in the vertical direction from the reference plane was calculated as the amount of warping, and the amount of warping was evaluated according to the following criteria. ○: Warpage is less than 4 mm △: Warpage is 4mm or more and less than 5mm ×: Warpage is 5mm or more
[0151] <Adhesion evaluation> The resin compositions prepared in the examples and comparative examples were compression molded on a 12-inch silicon wafer using a compression mold device (mold temperature: 130°C, pressure: 6 MPa, cure time: 10 minutes) to form a resin composition layer with a thickness of 300 μm. The resin composition layer was then heated at 180°C for 90 minutes to thermally cure. This resulted in a sample substrate including a silicon wafer and a cured layer of the resin composition. Subsequently, a high temperature and high humidity environmental test (HAST) was performed under conditions of 130°C, 85% RH, 96 hours. The cured layer after HAST was polished using sandpaper #180 until the cured layer had a thickness of 50 μm. The polished sample was cut into a test piece with a width of 1 cm square, and a φ2.7 mm stud pin with adhesive was placed perpendicular to the cured layer and heated at 150°C for 60 minutes to produce a test piece in which the stud pin and the cured layer were bonded. The obtained test pieces with stud pins were subjected to a vertical tensile test at a test speed of 0.1 kg / sec using a vertical tensile tester "ROMULUS" manufactured by QUAD GROUP Co., Ltd. Measurements were performed on five test pieces, and the average value was calculated and evaluated according to the following criteria. ○: Adhesion strength is 500kgf / cm 2 Exceeds. ×:500kgf / cm 2 less than.
[0152] <Evaluation of flow marks after molding> The resin compositions prepared in the Examples and Comparative Examples were compression molded on a 12-inch silicon wafer using a compression molding device (mold temperature: 130°C, pressure: 6 MPa, cure time: 10 minutes) to form a resin composition layer with a thickness of 300 μm (the area of the resin composition layer at this time was 14.6 cm × 14.6 × 3.14 = 45.844 cm 2 ) and the appearance of the resin composition layer was observed. When the area of the flow marks occupied less than 20% of the entire surface of the resin composition layer, it was marked as "good", and when it exceeded 20%, it was marked as "poor".
[0153] <Evaluation of resin surface unevenness after post-cure> The resin compositions prepared in the Examples and Comparative Examples were compression molded on a 12-inch silicon wafer using a compression molding device (mold temperature: 130°C, pressure: 6 MPa, cure time: 10 minutes) to form a resin composition layer having a thickness of 300 μm (the area of the resin composition layer at this time was 14.6 cm × 14.6 × 3.14 = 45.844 cm). 2 The resin composition layer was then heat-cured at 180°C for 90 minutes, and the appearance of the cured layer was observed. The cured layer surface was uniform and free of color unevenness, and the cured layer surface was marked with "◯" if it was not uniform due to color unevenness caused by separation of the resin or the like.
[0154] [Table 1] In the table, the content of the component (A-1) and the content of the component (B) are shown when the total amount of non-volatile components in the resin composition is taken as 100 mass %.
[0155] In Examples 1 to 6, it was confirmed that even when component (D) was not contained, the same results as in the above Examples were obtained, although to a different extent.
Claims
[Claim 1] (A-1) an epoxy resin having an epoxy equivalent of more than 400 g / eq. and not more than 1500 g / eq.; (B) an inorganic filler, and (C) a curing agent, The content of the component (A-1) is 0.2% by mass or more and less than 3% by mass, when the total amount of non-volatile components in the resin composition is 100% by mass, A resin composition, wherein the content of component (B) is 70 mass% or more when the total amount of non-volatile components in the resin composition is 100 mass%.
Citation Information
Patent Citations
Resin composition for molding, molded product for high voltage equipment by using the same and its production
JP1998060085A
Epoxy resin composition and semiconductor device
JP2002194061A
Epoxy resin composition having thermal degradation resistance
JP2009073933A
Resin composition for sealing electronic part, and electronic part device using it
JP2010018712A
Resin composition and three-dimensional laminated type semiconductor device using the resin composition
JP2018039992A